(3cJGH aj Gdabg efg aUd aj CMcGe GdNdd GdhGbY aj GdUdGIs - (3MSf GdNGbGfjs
(3ChdgG (B:s
(3HSe Gddg (B.. (3GdaUd GdSGHY aj GMcGe GdNdd GdhGbY aj GdUdGI GdhGLHI hgh dG jNdh EeG Cf jchf Yf YeO hbUO Edi GdNdd HdG aQb Hjf chfg YGedG HMceg Ce dG Ch Yf Sgh HZQhH GdeYfi Yf GdPgf (B...s
(3BNQgG (B:s
.. (3djS ef CMcGe GdSgh MJi jJMg GdGdJRGe HQaYg Hd gh ef ebJVjGJ GdCeQ GdChd GdeJYdb HPdec ShGA JLGhR eMdg GdCUdj Ce de jJLGhR hYdi cd aGdMeO ddg Ydi GdhaGbs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis